Poets without qualities: In search of the possible contemporaneity - Maffei, Luís (Revista de Letras, 2007)
A new trend appears in Portuguese literature - a new generation, wich is presented in an anthology named Poets without qualities. This poetry manifests a strong relationship with reality, and proposes, from a new poetic diction, the adoption of distinct parameters not only for the poem-making, but also for the recepction of poetry. Thus, a great deal of what was done in the twentieth century Portuguese literature will be replaced by a mode that deals with things that are prosaic, small and have no quality. However, certain decisive names of this literature´s history, such as Pessoa and Camões, will not disregarded.